2013
DOI: 10.1002/mnfr.201200838
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin‐free turmeric exhibits anti‐inflammatory and anticancer activities: Identification of novel components of turmeric

Abstract: Turmeric, a dried powder derived from the rhizome of Curcuma longa, has been used for centuries in certain parts of the world and has been linked to numerous biological activities including antioxidant, anti-inflammatory, anticancer, antigrowth, anti-arthritic, anti-atherosclerotic, antidepressant, anti-aging, antidiabetic, antimicrobial, wound healing, and memory-enhancing activities. One component of turmeric is curcumin, which has been extensively studied, as indicated by more than 5600 citations, most of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
187
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(201 citation statements)
references
References 121 publications
6
187
0
8
Order By: Relevance
“…Curcumin (1,7‐bis[4‐hydroxy‐3‐methoxyphenyl]‐1,6‐heptadiene‐3,5‐dione) is scientifically known as diferuloylmethane, derived from the rhizomes of C. longa . Curcumin is the main active component in turmeric which constitutes for approximately 2–5% of turmeric . Curcumin contains three main compounds—80% curcuminoid complex, 17% dimethoxy‐curcumin, and 3% bisdemethoxy‐curcumin .…”
Section: Protective Actions Of Curcuminmentioning
confidence: 99%
“…Curcumin (1,7‐bis[4‐hydroxy‐3‐methoxyphenyl]‐1,6‐heptadiene‐3,5‐dione) is scientifically known as diferuloylmethane, derived from the rhizomes of C. longa . Curcumin is the main active component in turmeric which constitutes for approximately 2–5% of turmeric . Curcumin contains three main compounds—80% curcuminoid complex, 17% dimethoxy‐curcumin, and 3% bisdemethoxy‐curcumin .…”
Section: Protective Actions Of Curcuminmentioning
confidence: 99%
“…Pharmacokinetic results showed that plasma curcumin levels in mice fed with turmeric extract were the highest ones (Aggarwal et al, 2013; Yue et al, 2016b). Interestingly, the combination of curcumin and turmerones abolishes tumor formation when fed to a dimethyl-hydrazine-initiated and DSS-promoted mouse model of CRC (Murakami et al, 2013).…”
Section: Curcuminmentioning
confidence: 99%
“…The extraction yields of five sesquiterpenes in RC, including curcumenone, curcumenol, curdione, curzerenone and furanodienone, were used to evaluate the quality of the extract, in consideration of their antiinflammatory and anticancer activities (Aggarwal et al, 2013) and protective effects on liver (Morikawa et al, 2002) and alcohol-induced drunkenness (Kimura et al, 2013). On the other hand, as the chemical compositions and bioactivities of the volatile compounds in FG were rarely reported, the extraction yields of the compounds in FG were not considered in this work.…”
Section: Design Of Experimentsmentioning
confidence: 99%